Balancing a Hybrid Business Model: The Search for Equilibrium at Cafédirect - Davies, Iain A. (Journal of business ethics, 2019)
This paper investigates the difficulties of creating economic, social, and environmental values when operating as a hybrid venture. Drawing on hybrid organizing and sustainable business model research, it explores the implications of alternative forms of business model experimented with by farmer owned, fairtrade social enterprise Cafédirect. Responding to changes and challenges in the market and societal environment, Cafédirect has tried multiple business model innovations to deliver on all three forms of value capture, with differing levels of success. This longitudinal case study, therefore, provides a contribution to our understanding of how business models enact hybrid mission, providing a platform for triple-bottom-line value capture. In doing so, we are able to expand on the normative understandings of integrating hybrid objectives, and the complications of multiple types of value capture.